RANCANGAN BANGUN SISTEM INFORMASI PRODUKSI AYAM PETELUR DENGAN MENGGUNAKAN FRAMEWORK CODEIGNITER - Teguh Martono, Kurniawan Martono; Windasari, Ike Pertiwi (Jurnal Sistem Komputer, 2018)
Chicken eggs are one source of animal protein that is easy to obtain and widely consumed by the community. Chicken eggs consumed in Indonesia consist of chicken and chicken. This opportunity became one of the causes of the emergence of many breeders of laying hens. Detailed processing production results cause problems for farmers. Information technology is one technology that is growing rapidly and widely used in helping activities in various sectors. One such sector is the field of laying hens. The use of information technology aims to solve a problem experienced by breeders and also to improve the effectiveness and efficiency when doing a job. Information technology in this case also has the following functions Capture, Processing, Generating, Storage, and Transmissions. To know the performance of the system that has been built then done the testing process. Test methods are performed using functionality testing. The results of this test results that the system has been built in accordance with the initial design. Performance of the system is running in accordance with its functionality.